A High Gain Concurrent Dual-band Low-Noise Amplifier in 130-nm BiCMOS Technology - Kurniawan, Taufiq Alif; Maritza, Afiya (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
This paper presents a fully integrated concurrent 15/30-GHz dual-band low-noise amplifier (LNA). The proposed concurrent LNA IC is designed and simulated in 130-nm BiCMOS technology. The new passive LC notch filter is proposed to realize high gain and low noise figure over dual-band frequency, simultaneously. The simulated BiCMOS LNA IC has exhibited peak gains of 30.1/23.7 dB at 15/30-GHz, respectively, with 20-mW power consumption from 1-V supply. The concurrent dual-band LNA achieves noise figure of 2.2/2.9-dB and IIP3 of -18.2/-8.8 dBm at the respective passbands. Therefore, the proposed dual band concurrent LNA IC is applicable to front-end RF receivers for Ku-Band and Ka-Band systems.